Case Report: effect of lumasiran treatment in a late preterm baby with antenatal diagnosis of primary hyperoxaluria type 1 - Taroni, Francesca; Berrettini, Alfredo; Gnech, Michele; Rella, Francesca; Manzoni, Gian Antonio; Montini, Giovanni (Frontiers in Pediatrics, 2024)
Background. Primary hyperoxaluria type 1 (PH1) is a rare disease with autosomal recessive transmission, characterized by increased urinary excretion of oxalate, resulting in chronic kidney disease secondary to recurrent urolithiasis, nephrocalcinosis, and accumulation of oxalate in various organs and tissues (systemic oxalosis). Since 2020, an innovative pharmacological approach, lumasiran, has been added to the therapeutic armamentarium (dialysis, and liver-kidney transplantation). The purpose of this paper is to describe the effect of lumasiran initiated at 10 days of life in a newborn, with prenatally diagnosed PH1.A female fetus was prenatally diagnosed with hyperoxaluria type 1, based on family history and genetic testing. Her brother had the onset of the disease at 2 months of age and underwent liver and kidney transplantation at 13 months and 8 years of age respectively.The baby was born late preterm at 36 weeks + 4 days of gestation via spontaneous labor and lumasiran for compassionate use was started on the tenth day of life. At 20 months of age, the baby shows normal urinary oxalate values and kidney function, while plasma oxalate under the threshold of oversaturation. There are no signs of systemic oxalosis.Early use of lumasiran in young infants, who do not yet show signs of the disease, represents a therapeutic challenge for the pediatric nephrologist to date. It remains to be clarified the ability of the drug to act on the hepatocyte of the newborn and the most appropriate dosage to be used in this very young babies.